THE QURANIC PERSPECTIVES ON WEALTH INVESTMENT IN REALIZING MAQASHID SHARI'AH - Safrudin Halimy Kamaluddin; Meirison Meirison (Fakultas Agama Islam Universitas Wiralodra, 2021)
Knowledge of the Maqasid of Sharia comes from the texts of the Qur'an and Sunnah, and its roots are deeply rooted in the consciousness of the first generations of Muslims, especially in the first centuries. The verses of the Qur'an are rich in statements of statutory regulations, and the hadiths of the Prophet are full of clarifications of importance arising from the commands and instructions of the Maqashid of Sharia. Text is the first, strongest, and highest way to express the will of Allah S.W.T. Therefore, this study aims to collect